Analisis Komoditas Unggulan Perikanan Tangkap, Perikanan Tangkap Laut Dan Perikanan Budidaya Di Kabupaten Trenggalek Provinsi Jawa Timur - Putra, Angga Pratama; Wijayanti, Regita Faridatunisa; Hartati, Fadjar Kurnia (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2024)
This study was conducted to identify the most important fisheries commodities in Trenggalek Regency and to provide data to related parties and investors interested in this sector. Trenggalek Regency is included in the category of districts that have a strategic location. Data analysis uses Location Quotient by utilizing data on the value of capture fisheries, sea capture fisheries, and aquaculture fisheries available from BPS Trenggalek Regency in 2023. The results of the analysis explain that the superior commodities for capturing fisheries at sea in Trenggalek Regency are in Panggul, Munjungan, and Watulimo. Meanwhile, the leading capture fishery commodities in Trenggalek Regency for inland public water fisheries are in Panggul, Munjungan, Kampak, Karangan, Suruh, Gandusari, Durenan, Pogalan, Trenggalek, Tugu, and Bendungan subdistricts. The leading marine fisheries commodities in Trenggalek Regency include Cakalang Fish in Watulimo District, Tuna Fish in Munjungan and Watulimo Districts, Tuna Fish in Watulimo District, and Lobster in Panggul, Munjungan, and Watulimo Districts. Meanwhile, superior aquaculture commodities include marine Floating nets in Watulimo District and semi-intensive ponds in Panggul, Munjungan, and Watulimo Districts. There are 9 sub-districts that need to be included in the 2021–2026 Trenggalek Regency RPJMD for land and freshwater fish cultivation areas, namely Munjungan, Watulimo, Kampak, Karangan, Suruh, Gandusari, Pogalan, Trenggalek, and Tugu sub-districts. Meanwhile, the capture fisheries and coastal aquaculture areas between the RPJMD and the research results are the same, namely that there are 3 sub-districts that have superior commodities, namely Panggul, Munjungan, and Watulimo sub-districts.